Nitrogen Management in a Maize-Groundnut Crop Rotation of Humid Tropics: Effect on N2O Emission - M.I. Khalil; A.B. Rosenani; O. Van Cleemput; C.I. Fauziah; J. Shamshuddin (The Scientific World Journal)
Development of appropriate land management techniques to attain sustainability and increase the N use efficiency of crops in the tropics has been gaining momentum. The nitrous oxides (N2Os) affect global climate change and its contribution from N and C management systems is of great significance. Thus, N transformations and N2O emission during maize-groundnut crop rotation managed with various N sources were studied. Accumulation of nitrate (NO3 –) and its disappearance happened immediately after addition of various N sources, showing liming effect. The mineral N retained for 2–4 weeks depending on the type and amount of N application. The chicken manure showed rapid nitrification in the first week after application during the fallow period, leading to a maximum N2O flux of 9889 μg N2O-N m–2 day– 1. The same plots showed a residual effect by emitting the highest N2O (4053 μg N2O-N m–2 day– 1) during maize cultivation supplied with a halfrate of N fertilizer. Application of N fertilizer only or in combination with crop residues exhibited either lowered fluxes or caused a sink during the groundnut and fallow periods due to small availability of substrates and/or low water-filled pore space (<40%). The annual N2O emission ranged from 1.41 to 3.94 kg N2O-N ha–1; the highest was estimated from the chicken manure plus crop residues and half-rate of inorganic N-amended plots. Results indicates a greater influence of chicken manure on the N transformations and thereby N2O emission.